2008
DOI: 10.1177/1078345808316863
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Chlamydia trachomatis Screening and Treatment in a Juvenile Detention Center

Abstract: Screening and treatment for Chlamydia trachomatis in the incarcerated population is important and challenging. The goal of this study was threefold: (a) investigate the usefulness of screening asymptomatic juveniles; (b) examine the feasibility of completing treatment in high turnover juvenile correction facilities; and (c) assess the strengths and weaknesses of the current screening and treatment program in a juvenile detention center relative to the Centers for Disease Control and Prevention guidelines. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…HIV prevalence in US justice populations is 2–5 (CDC, 2012b ; Martin, O'Connell, Inciardi, Surratt, & Beard, 2003 ; Maruschak, 2011 ; New York State Department of Health, 2010 ; Spaulding et al, 2009 ) times higher than in the general population, and justice-involved young adults (JIYA) aged 18–24 are at particular risk (Dembo, Belenko, Childs, Greenbaum, & Wareham, 2010 ; Elkington et al, 2008 ; Frye, Wallace, Chavez, & Luce, 2008 ; Joesoef, Kahn, & Weinstock, 2006 ; Kahn et al, 2005 ; Morris et al, 1995 ; Pack, DiClemente, Hook III, & Oh, 2000 ; Romero et al, 2007 ). Many JIYA reside in neighborhoods with high community HIV viral loads, exposing them to high risk sexual networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV prevalence in US justice populations is 2–5 (CDC, 2012b ; Martin, O'Connell, Inciardi, Surratt, & Beard, 2003 ; Maruschak, 2011 ; New York State Department of Health, 2010 ; Spaulding et al, 2009 ) times higher than in the general population, and justice-involved young adults (JIYA) aged 18–24 are at particular risk (Dembo, Belenko, Childs, Greenbaum, & Wareham, 2010 ; Elkington et al, 2008 ; Frye, Wallace, Chavez, & Luce, 2008 ; Joesoef, Kahn, & Weinstock, 2006 ; Kahn et al, 2005 ; Morris et al, 1995 ; Pack, DiClemente, Hook III, & Oh, 2000 ; Romero et al, 2007 ). Many JIYA reside in neighborhoods with high community HIV viral loads, exposing them to high risk sexual networks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Adolescent Trial Network (ATN) data found that one in every three HIV+ youth had prior justice involvement (Gamarel et al, 2016 ). Furthermore, JIYA have higher rates of HIV risk behaviors than general population youth (Elkington et al, 2008 ; Morris et al, 1995 ; Pack et al, 2000 ; Romero et al, 2007 ), and much higher rates of STIs (4%–48%) (Dembo et al, 2010 ; Frye et al, 2008 ; Joesoef et al, 2006 ; Kahn et al, 2005 ). With high HIV risk behaviors, and residence in poor, high-prevalence communities, JIYA may be more likely to be HIV+ than general population youth, but are just as likely to be unaware of their status (Van Handel, Kann, Olsen, & Dietz, 2016 ; Zanoni & Mayer, 2014 ).…”
Section: Introductionmentioning
confidence: 99%